2019
DOI: 10.1002/1878-0261.12532
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly expressed PLOD1 promotes cancer aggressiveness in bladder cancer: a potential prognostic marker and therapeutic target

Abstract: Bladder cancer ( BC ) is the ninth most malignant tumor worldwide. Some BC patients will develop muscle‐invasive BC ( MIBC ), which has a 5‐year survival rate of approximately 60% due to metastasis. As such, there is an urgent need for novel therapeutic and diagnostic targets for MIBC . Analysis of novel antitumor micro RNA (mi RNA )‐mediated cancer ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 47 publications
4
32
0
2
Order By: Relevance
“…Another study found that miR-140-5p could directly bond with the 3′-UTR of PLOD1 and decreased the expression of PLOD1 in T24 and BOY cells. Small interfering RNA-mediated PLOD1 knockdown could dramatically inhibit migration and invasion of T24 cells [ 25 ]. These results were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that miR-140-5p could directly bond with the 3′-UTR of PLOD1 and decreased the expression of PLOD1 in T24 and BOY cells. Small interfering RNA-mediated PLOD1 knockdown could dramatically inhibit migration and invasion of T24 cells [ 25 ]. These results were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…revealed that overexpression of PLOD1 was closely related to poor survival and downregulation of PLOD1 can decrease the progression of BC [15]. CKB was participated in metabolic processes involving glycolysis and could serve as a biomarker for predicting tumor progression [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PLOD1 encodes lysyl hydroxylases, which are crucial for collagen biosynthesis, cross-linking, and deposition and can promote cancer progression and metastasis [39]. Yamada Y et al revealed that overexpression of PLOD1 was closely related to poor survival and downregulation of PLOD1 can decrease the progression of BC [40]. CKB was participated in metabolic processes involving glycolysis and could serve as a biomarker for predicting tumor progression [41].…”
Section: Discussionmentioning
confidence: 99%